Implications of genetics and current protected areas for conservation of 5 endangered primates in China - Zhijin Liu; Guangjian Liu; Christian Roos; Ziming Wang; ZuoFu Xiang; Pingfen Zhu; Boshi Wang; Baoping Ren; Fanglei Shi; Huijuan Pan; Ming Li (Conservation Biology, 2015)
Most of China's 24–28 primate species are threatened with extinction. Habitat reduction and fragmentation are perhaps the greatest threats. We used published data from a conservation genetics study of 5 endangered primates in China (Rhinopithecus roxellana, R. bieti, R. brelichi, Trachypithecus francoisi, and T. leucocephalus); distribution data on these species; and the distribution, area, and location of protected areas to inform conservation strategies for these primates. All 5 species were separated into subpopulations with unique genetic components. Gene flow appeared to be strongly impeded by agricultural land, meadows used for grazing, highways, and humans dwellings. Most species declined severely or diverged concurrently as human population and crop land cover increased. Nature reserves were not evenly distributed across subpopulations with unique genetic backgrounds. Certain small subpopulations were severely fragmented and had higher extinction risk than others. Primate mobility is limited and their genetic structure is strong and susceptible to substantial loss of diversity due to local extinction. Thus, to maximize preservation of genetic diversity in all these primate species, our results suggest protection is required for all sub‐populations. Key priorities for their conservation include maintaining R. roxellana in Shennongjia national reserve, subpopulations S4 and S5 of R. bieti and of R. brelichi in Fanjingshan national reserve, subpopulation CGX of T. francoisi in central Guangxi Province, and all 3 T. leucocephalus sub‐populations in central Guangxi Province.